Comparison between endoscopic and microscopic type 1 tympanoplasty using temporalis fascia graft - Surapaneni Sai Poojyata; Pradipt Ranjan Sahoo; Khageswar Rout; Nishikant Pradhan; Kabikanta Samantaray; Manas Ranjan Rout (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The outcomes of endoscopic vs. microscopic type 1 tympanoplasty in patients with central perforation in the tympanic membrane and conductive hearing loss will be compared. Methods: This study was conducted in the Department of Otorhinolaryngology at a tertiary care hospital and medical college in Odisha. This study was a hospital-based, single-centered, simple randomized control trial. A total of 100 cases of chronic suppurative otitis media were randomized into endoscopic and microscopic assisted tympanoplasty groups (50 each) after taking proper informed consent. The duration of the study was from September 2019 to August 2021. Results: Out of 100 surgeries, there was one failure of graft uptake, and the patient belonged to the endoscopic group. Operative time was significantly shorter in the endoscopic group as compared to the microscopic group. There was no significant difference in terms of graft uptake and hearing improvement among the two groups. Conclusion: Both microscopic and endoscopic tympanoplasty have their own advantages and disadvantages. Endoscopic tympanoplasty offers slight benefits over microscopic tympanoplasty in terms of shorter duration, less granulation, less post-operative pain and a wider angled view, but it has inherent disadvantages being a single-handed procedure. Unlike a microscope, an endoscope is easily transportable; hence, it can be ideally used in camps conducted in remote places.